A Prototype-Driven Approach for e-Waste Redistribution - Heni Rachmawati Santoso; Adriza Rafly Azlami; Yuli Fitrisia; Wenda Novayani (Jurnal Komputer Terapan, 2026)
The rise of electronic waste (e-Waste) poses a serious environmental challenge due to the public's lack of awareness and limited access to standardized recycling facilities. This study proposes a community-based E-Waste redistribution model integrated with Circular Economy principles, implemented through a mobile platform. To ensure responsible E-Waste management, this architecture features a dedicated redistribution flow connecting end-users directly with verified recyclers. Furthermore, Location-Based Services (LBS) are implemented not merely for mapping, but as a spatial proximity-matching algorithm using the Haversine formula to optimize logistics. The system was developed using a prototyping methodology, encompassing comprehensive user requirement identification and two iterative design cycles based on qualitative user feedback. Functional evaluation via black-box testing validated a 100% success rate across all system integration scenarios. Moreover, usability testing involving 21 demographically targeted respondents, evaluated using a custom-developed questionnaire and yielded a feasibility score of 91.5%. These findings indicate a high level of user acceptability and interface effectiveness. Ultimately, this research contributes an algorithmic and architectural framework for communitydriven e-Waste management, establishing a viable digital solution for sustainable waste redistribution.